Medical and pharmacy students' perceptions of the grading and assessment practices - MITONGA KABWEBWE, Honoré; KASANDA, Choshi Darius; VEII, Kazuvire; ZIMBA, Roderick (Frontiers in Psychology, 2013)
Many students at the University of Namibia have frequently complained about ineffective assessment practices used at the institution. On many occasions, these complaints have not been substantiated with evidence of any kind. The purpose of this study was to obtain some empirical evidence that would ascertain undergraduate students’ perceptions of the University of Namibia’s grading and assessment practices. Using a structured scaled questionnaire, data were obtained from a representative sample of the University’s undergraduate students studying for Medical and Pharmacy degrees. The questionnaire items covered matters related to students’ experiences of assessment practices, feedback on assessment tasks, reliability and validity of assessment tools used by lecturers, efficacy of processes of administering examinations, perceptions of irregular and unfair assessment practices, impact of assessment regimes on students’ cost of studies, motivation, morale, rate of progression in studies and graduation, the degree of compliance with assessment ethics and on academic quality assurance. According to the data reported in this article, the majority of the respondents perceived that the Schools of Medicine and Pharmacy at the University of Namibia applied assessment practices that yielded reliable and valid results. This was the case because most lecturers in the two schools used appropriate assessment tools and provided their students with prompt and informative feedback on the results of assignments, tests and examinations. In addition, most respondents reported that whereas examination procedures used in the two schools were efficient and effective, lecturers graded examination scripts fairly. These and other results are discussed in the article to communicate the message that the assessment procedures used in the Schools of Medicine and Pharmacy at the University of Namibia would promote effective learning and understanding amongst students as they were of high quality.